1993
DOI: 10.1016/0092-8674(93)90536-y
|View full text |Cite
|
Sign up to set email alerts
|

The segment polarity gene hedgehog is required for progression of the morphogenetic furrow in the developing Drosophila eye

Abstract: Cell-type specification in the Drosophila compound eye begins at the morphogenetic furrow. The furrow sweeps across the developing eye epithelium and is coincident with four classes of cellular events: coordinated changes in cell shape, changes in gene expression, synchronization of the cell cycle, and the specification of a regular array of ommatidial founder cells. The molecular mechanisms that induce these events in the developing eye have hitherto been unknown. We identify here a gene specifically required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
241
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(251 citation statements)
references
References 54 publications
8
241
2
Order By: Relevance
“…2D). The reason for this differential effect is unknown; however, it has been shown that initiation of development at the posterior margin is driven by dpp (Wiersdorff et al 1996; Chanut and Heberlein 1997; Pignoni and Zipursky 1997), whereas its internal propagation depends on hh (Heberlein et al 1993(Heberlein et al , 1995Ma et al 1993). Moreover, clones of cells mutant for the Dpp receptor thick veins proliferate significantly only when they include the posterior margin (Burke and Basler 1996).…”
Section: Eyelid Affects Patterning Of the Eye Imaginal Discmentioning
confidence: 99%
See 1 more Smart Citation
“…2D). The reason for this differential effect is unknown; however, it has been shown that initiation of development at the posterior margin is driven by dpp (Wiersdorff et al 1996; Chanut and Heberlein 1997; Pignoni and Zipursky 1997), whereas its internal propagation depends on hh (Heberlein et al 1993(Heberlein et al , 1995Ma et al 1993). Moreover, clones of cells mutant for the Dpp receptor thick veins proliferate significantly only when they include the posterior margin (Burke and Basler 1996).…”
Section: Eyelid Affects Patterning Of the Eye Imaginal Discmentioning
confidence: 99%
“…Progression of the furrow depends on the expression of hh by differentiating photoreceptors located posterior to the MF (Heberlein et al 1993;Ma et al 1993;Heberlein et al 1995). Hh protein induces more anteriorly-located cells to differentiate and themselves express hh, thereby creating a cycle of induction that moves the furrow across the eye disc.…”
mentioning
confidence: 99%
“…The impetus for asking the first question lies in the fact that Hh signaling is also required for furrow initiation (Ma et al, 1993;Heberlein et al, 1993;Chanut and Heberlein, 1995;Heberlein et al, 1995;Ma and Moses, 1995;Pan and Rubin, 1995;Strutt et al, 1995;Wehrli and Tomlinson, 1995). However, expression of emc under the control of either dpp or ey enhancers, both of which drive expression at the posterior margin of the disc (Blackman et al, 1991;Hauck et al, 1999), failed to have any observable effect on furrow initiation (supplementary material Fig.…”
Section: Emc Both Regulates and Cooperates With Wg Signaling To Prevementioning
confidence: 99%
“…Progression of the furrow and dpp activation are both dependent upon Hh signaling (Heberlein et al, 1993;Ma et al, 1993;Heberlein et al, 1995;Domínguez and Hafen, 1997;Borod and Heberlein, 1998). We attempted to ascertain whether furrow acceleration and increased dpp transcription within emc-null clones are due to elevated Hh signaling.…”
Section: Emc Controls the Pace Of Furrow Movement Through Regulation mentioning
confidence: 99%
“…Furthermore, no defects in the positioning of mitochondria or nuclei, were observed. Overall, although the organization of photoreceptor cell cytoplasm was mildly affected by a loss of KHC, ultrastructural changes known to correlate with serious disruptions of the recycling and secretory pathways were not seen.During eye development, cell specification is controlled through cell-cell signaling, which requires membrane proteins and secreted morphogens (Heberlein et al, 1993(Heberlein et al, , 1995Ma et al, 1995) (reviewed by Dickson and Hafen, 1993;Wolff and Ready, 1993). If photoreceptors in Khc null test clones were aberrant or missing as a consequence of poor signaling, the effect should have been nonautonomous: mutant cells could cause defects in neighboring wild-type cells, or wildtype cells could rescue the defects in neighboring mutant cells.…”
mentioning
confidence: 99%